PENGEMBANGAN MODAL SOSIAL UNTUK MENDUKUNG PENANGGULANGAN KENAKALAN SISWA - Muslimin, Fatkhul; Novi Ismiasih; Nafhatul Mawardah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2024)
This research aims to describe the forms and ways of dealing with student delinquency along with the use of social capital to support the way of dealing with student delinquency at MAN 1 GRESIK. The method used is a qualitative method. Research data was obtained through observation, interviews and documentation. The research results show that the dominant forms of delinquency include being late for school or class, not entering school without explanation, not wearing a uniform according to school regulations. Dealing with delinquency is carried out in preventive and repressive ways. Social capital is used to develop teachers' commitment to presenting a good personality to students, collaborating with students in maintaining a conducive learning atmosphere, providing deep understanding for students who violate, developing students' self-confidence, responsibility and honesty.